REAFFIRMATION OF THE METHODS AND SPIRIT OF LITERARY CRITICISM : (CONTRIBUTION TO THE INTERPRETATION OF THE HISTORY OF SERBIAN LITERATURE BY JOVAN DERETIĆ) (Heritage, 2021)
The paper discusses five monographs by Jovan Deretić, which the author considers "accompanying books" of his History of Serbian Literature. These are: Marko Kraljević's riddle - about the nature of historicity in Serbian folk epics, The path of Serbian literature - identity, borders, aspirations, Poetics of Serbian literature, Serbian folk epics and Etudes from old Serbian literature.In this paper, we analyze them as a contribution to the interpretation of the History of Serbian Literature, the most comprehensive history of literature in Serbian science to the extent that they are important as proof of Deretić's great synthesis and consideration of the function of literary criticism in Serbian culture. An important definition of the "accompanying books" is provided by the author in their prefaces and notes. It is summarized in the theoretical and applied level in the process of considering important issues of Serbian literary history: periodization and classification of literature, poetic or historical determinants and the significance of particular epochs, writers, or genres.A review of the critical evaluation of Serbian literature and historical and cultural heritage in the accompanying books shows that Deretić pragmatized his scientific thought and reaffirmed literary criticism, directing it "for the benefit of the people." This means that he gave it a practical and social function and intended it "for a distant generation".
Keywords: Jovan Deretić, history of Serbian literature, epics, poetics, folk literature, old literature, identity, criticism, culture